International Finance Corporation Country Diagnostics and Strategies under IFC 3.0 : An Early-Stage Assessment : Approach Paper - Independent Evaluation Group (Washington, DC : World Bank, 2022)
In December 2016, the International Finance Corporation (IFC) introduced its latest strategy, IFC 3.0, which aimed to enhance IFC’s development impact by creating “new and stronger markets for private sector solutions” (IFC 2019) and “mobilizing private capital at significant scale” (IFC 2021) where it is needed the most. To achieve IFC 3.0’s aims of market creation and private capital mobilization at scale, IFC recognized it would need new tools and analytical capabilities to: (i) Develop a deeper understanding of the constraints limiting private sector solutions and opportunities in each country’s economy, including in key enabling and productive sectors; and (ii) Allow for a more strategic selection, sequencing, and implementation of its activities and stronger coordination across the World Bank Group. At the country level, IFC 3.0’s tools included a new diagnostic instrument, the Country Private Sector Diagnostic (CPSD), and a new strategy instrument, the IFC Country Strategy. The objective of the evaluation is to assess whether IFC Country Strategies and CPSDs have enhanced IFC’s ability to create markets and mobilize capital at scale and have informed Bank Group collaboration on private sector development. The evaluation will focus on IFC Country Strategies and CPSDs completed since their inception in fiscal year (FY)18. The evaluation will cover all 50 IFC Country Strategies and the 31 CPSDs completed between FY18 and December 31, 2021.